REGISTER PETANI PADI SAAT MUSIM PANEN MASYARAKAT JAWA DESA PARIT KELADI KABUPATEN KUBU RAYA - Pandu Antero; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this research is the rice register during the harvest season of the Javanese community of Desa Parit Keladi, Kabupaten Kubu Raya. The problem of this research is the type of register, register element, register factor of rice farmers during the harvest season of the Javanese community of Desa Parit Keladi, Kabupaten Kubu Raya, and the implications of learning at school? The method used in this research is descriptive qualitative form. The data collection techniques of this study were competent see engendant, competent free engendant, record, and note taking techniques. The tools used in this study are cameras and stationery. The results of the study are classified into two types of registers, namely open registers and closed registers which are divided into three closed registers and twelve open registers. This study found fifteen registers, wiwiti, ngedos, benteli, ngungkal, ngaret, minggiri, ngunjukne, nyunggi, nyurung, numpuk, ngadahi, mepe, ngorak-ngarik, ngentas, dan nyimpen. Conclusions in this study are the types of registers, register elements, register factors, and learning implications. Keywords: Harvest Season, Javanese People, Register of Rice Farmers